Minimally invasive surgery for intradural extramedullary spinal cord pathologies: A case series and technical note. (March 2022) - Kelly, Ryan; Fayed, Islam; Conte, Anthony; Rock, Mitchell; Nair, Nathan; Voyadzis, Jean Marc; Sandhu, Faheem; Anaizi, Amjad
Highlights: Intradural extramedullary pathology can be treated with minimally invasive surgery. Minimally invasive surgery has comparable outcomes to open procedures. Minimally invasive surgery can be completed with standard operating room equipment. Abstract: Background: Intradural spinal cord pathologies have traditionally been managed with open surgical procedures and require the completion of a durotomy. Minimally invasive techniques are emerging as alternative procedures with the goal of reducing complications, but often require specialized equipment with additional training. Methods: We conduct a single institution retrospective review from 2016 to 2019 of patients undergoing minimally invasive durotomy closure for intradural extramedullary pathologies using a novel technique that utilizes standard operating room equipment. This cohort is compared to a cohort of patients treated with a traditional open approach. Results: Patients treated with minimally invasive surgery (MIS) had no statistically significant differences in baseline characteristics compared to patients treated with open procedures. Patients treated with MIS had decreases in complication rates, estimated blood loss, and length of stay in the hospital compared to the patients treated with open procedures, but these differences did not reach levels of statistical significance. Conclusions: Our novel MIS technique for intradural extramedullary pathologies appears to be safe and effective in creating a watertight dural closure using standard operating room equipment, while avoiding the costs and training associated with specialized equipment and possibly improving surgical outcome measures when compared to open approaches.